Performance of thermoelectric generator system to generate electrical output from a low-grade waste heat temperature under linear and swirling waste heat streams / Muhammad Hadrami Hamdan ... [et al.] - Hamdan, Muhammad Hadrami; Zamri, Nur Faranini; Remeli, Muhammad Fairuz; Mohd Hanim, Nabilah Huda; Mohd Fatmi Shah, Hafizah Jamilah; Wan Mohamed, Wan Ahmad Najmi (Universiti Teknologi MARA Cawangan Pulau Pinang, 2024)
A thermoelectric generator (TEG) module converts heat directly into electrical energy. Waste heat from a process is a viable heat source for TEG modules to support the energy sustainability agenda. A module was designed to recover low-temperature waste heat from a 1 kW fuel cell stack used in a mini hydrogen vehicle. The module was constructed using a single TEG cell that receives heat directly on its surface from the waste heat stream, coupled with a heat pipe connected to a finned heat sink to effectively cool the cold junction of the TEG cell. This research presents a comparison of the module characteristics when it is operated under direct impinging jet flow and swirl flow waste heat streams at 60°C, while the cold junction of the cell is cooled under stationary vehicle conditions (natural convection cooling) and cruising conditions (forced convection cooling) at an air speed of 5 m/s. Results indicate that the swirling effect increases the maximum power point (MPP) by 60%. The introduction of swirl to the heating stream is a viable approach to significantly enhance the recovery of low-grade waste heat using TEG. However, the MPP shows a greater increase of 70 to 80% due to the forced cooling effect, indicating that cold junction cooling has a more significant influence on the MPP compared to the swirl effect.